When widows speak through self disclosure and social support in #SaveJanda community - Lim, Jolynn Alexander; Primadini, Intan (Universitas Padjadjaran, 2026)
Background: Interpersonal communication is central to how individuals navigate major life transitions. For widows in patriarchal societies, communication serves as a crucial means for managing grief, navigating shifts in identity, and pursuing emotional connection. In widow-support communities, processes such as trust-building, relational closeness, and self-disclosure shape how members share experiences and obtain social support. However, little is known about how self-disclosure unfolds among widows in peer-based community settings in Indonesia. Purpose: This study investigates the self-disclosure practices of widows within the #SaveJanda community as an interpersonal communication strategy for obtaining social support. Methods: Using a qualitative interpretive paradigm, this study adopted Robert E. Stake’s case study approach. The participants were five widows who were actively involved in the community and were selected through purposive sampling. Data was collected through in-depth interviews and were analyzed thematically. Results: The findings reveal that widows progress through stages of interpersonal communication consistent with Social Penetration Theory (SPT). Feelings of safety, mutual empathy, and shared life experiences facilitate deeper self-disclosure, enabling participants to develop closeness and trust. These communicative processes facilitate the acquisition of emotional, informational, and practical support. Conclusion: Self-disclosure is a key interpersonal strategy for widows to obtain emotional and social support and to establish meaningful connections within the community. Implications: Theoretically, this research strengthens the application of SPT. Practically, it highlights the importance of creating emotionally safe environments that encourage sharing and support among widows.